Facilities management : effectiveness in outsourcing / Mohd Khairi Kurdi ... [et al.] - Kurdi, Mohd Khairi; Ma'arof, Khairul Anuar; Shuib, Mohammad Nasharudine; Ab Wahid, Abdul Muhaimin; Yusof, Ismail; Azli, Mohd Syhidi; Abdul Tharim, Asniza Hamimi; Jaffar, Noraidawati (2012)
Facility management is the integration of multiple disciplines necessary for the ensuring functionality of the land, buildings, infrastructure, furniture, equipment and fixtures of a company necessary for the operations of the business. It is the role of the Facility Management department to coordinate and oversee the safe, secure and environmentally sound operations and maintenance of these assets in a cost effective manner aimed at longterm preservation of the asset value. Therefore the aim of this paper is to overview the definitions and effectiveness in outsourcing facilities management. Data were obtained through questionnaire surveys to selected public higher education buildings' facilities management departments namely UPM, UM and UiTM. Findings of this study were presented in an integrated tabulated charts and tables. Ultimately, this research hoped to contribute a better understanding on the effectiveness of outsourcing in facilities management.